JEHD 2017
DOI: 10.15640/jehd.v6n3a7
|View full text |Cite
|
Sign up to set email alerts
|

Contemplative Pedagogy: Mindfulness Methodology in Education & Human Development

Abstract: Today"s children and adolescents live in a digital era, exposed to technology at a young age and often times maintain fast-paced lifestyles. Expectations for students in education have increased steadily in recent decades. In accordance with student lifestyles and heightened expectations in academia, education for children in P-12 has become consistently saturated with technological-based enhancements. As a result, educators continuously search for innovative pedagogical approaches, such as contemplative pedag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that students experiencing stress are not able to learn; their level of anxiety is so high that it is impossible for them to concentrate in class. Meditation reduces students' stress levels, inducing a change in brain waves and provoking more states of calm, i.e., a brain that functions better (Flores, 2017;Leon, 2008).…”
Section: Mindfulnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that students experiencing stress are not able to learn; their level of anxiety is so high that it is impossible for them to concentrate in class. Meditation reduces students' stress levels, inducing a change in brain waves and provoking more states of calm, i.e., a brain that functions better (Flores, 2017;Leon, 2008).…”
Section: Mindfulnessmentioning
confidence: 99%
“…Most of the works published to date include mindfulness practices individually (Flores, 2017;Park, Long, Chose, & Schallert, 2018), as something separate from the methodologies used to learn the contents and competences of a certain course.…”
Section: Goals Of the Projectmentioning
confidence: 99%
See 1 more Smart Citation